2013
DOI: 10.2466/09.10.pr0.113x22z4
|View full text |Cite
|
Sign up to set email alerts
|

Up- and Down-Regulation of Daily Emotion: An Experience Sampling Study of Chinese Adolescents' Regulatory Tendency and Effects

Abstract: The present study examined Chinese adolescents' emotion regulatory tendency and its effect, using an Experience Sampling Method. Participants comprised 72 Chinese adolescents (M age = 15.2 yr., SD = 1.7; 36 girls). Momentary emotional experience and regulation was assessed up to 5 or 6 times each day for two weeks. Results showed that participants tended to use up-regulation when they experienced positive emotion and habitually regulated their negative emotion by down-regulation. Also, adolescents who utilized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 33 publications
0
28
0
Order By: Relevance
“…Contra-hedonic motivation is defined as the tendency to enhance unpleasant emotions and suppress pleasant emotions. It is considered to be beneficial to emotional outcomes personally, and it is consistent with the core regulation goal of maintaining interpersonal harmony nationally (e.g., Deng et al, 2013). Mixed emotions could be the experiential consequence of contra-hedonic motivation (Miyamoto et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contra-hedonic motivation is defined as the tendency to enhance unpleasant emotions and suppress pleasant emotions. It is considered to be beneficial to emotional outcomes personally, and it is consistent with the core regulation goal of maintaining interpersonal harmony nationally (e.g., Deng et al, 2013). Mixed emotions could be the experiential consequence of contra-hedonic motivation (Miyamoto et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Such contra-hedonic motivation is more common among Chinese population. For instance, Deng et al (2013) found that, in a pleasant emotional event, Chinese adolescents who intentionally sacrificed their short-term hedonic needs would experience higher levels of pleasant emotions in a long-term time scale. However, some ethnic minorities in China, such as Mongolian Chinese, despite sharing a collective and interdependent culture with Han Chinese, allow and encourage the expression of happiness in front of others (Li et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Third, down‐regulating facial expression might be related to psychological dysfunctions for Western participants, but not for Chinese participants (Soto et al, ). Chinese adolescents who use down‐regulation more frequently in their daily life reported higher pleasant experience (Deng et al, ). Taking together, emotion down‐regulation avoids the potential harms of interpersonal harmony, meets the Chinese beliefs of emotions and provides benefits to psychological functions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, attaining long‐term benefits demand Chinese to sacrifice their short‐term hedonic needs (e.g. suppressing happiness for getting good grade on an exam and working even harder for the next academic challenge, Deng, Sang, & Luan, ).…”
Section: Cultural Differences In Emotional Preferencesmentioning
confidence: 99%
“…Spencer‐Rodgers et al () found that Chinese reported the mixed emotions of pleasant and unpleasant more frequently than European Americans. Also, the relations between down‐regulated pleasant emotions and positive emotional experiences were wearker among Chinese (Deng et al, ). In fact, some findings suggests that a given emotion contains both negativity and positivity.…”
Section: Cultural Differences In Emotional Preferencesmentioning
confidence: 99%